INDICADORES ECONÔMICOS E SOCIAIS NA UGRHI-22 NO PERÍODO DE 2004 A 2016: OS EFEITOS DA EXPANSÃO DA CANA-DE-AÇÚCAR - EVANGELISTA, C. R. L. (2016)
In the last decades the cultivation of sugarcane has stood out in relation to the territorial expansion in the state of São Paulo. As a result, discussions about their effects on growth and economic development in the regions where it has a larger share of agricultural activity have become increasingly popular. Facing this context, the Pontal do Paranapanema region became a protagonist and object of research in relation to the advance of sugarcane and its effects on growth and economic development. The objective of this study was to evaluate the effects of the expansion of sugarcane on the growth and economic development indicators of UGRHI-22 in the period from 2004 to 2016. For this purpose, the Internal Product Total Gross GDP, Gross Domestic Product - Agricultural GDP and as indicators of economic development were considered the Municipal Human Development Index - IDHM and the Paulista Index of Social Responsibility - IPRS. Pearson's multiple correlation and Pearson correlation statistical techniques were used as methods for data analysis. As results, it was obtained that the cultivation of sugarcane in the UGRHI-22 occurred in an increasing form, with advance of 408%. Through statistical analyzes of multiple comparison, it was observed that the indicators of cultivation of sugarcane, Total GDP, Agro GDP and IPRS showed different behaviors in the analyzed period. However, the HDI showed the same behavior in the years 1991, 2000 and 2010, whose periods presented different levels of sugarcane cultivation, indicating that the evolution of the crop did not influence the evolution of the economic development of the region studied. Pearson's statistical analysis of linear correlation resulted in the absence of a significant correlation between the indicators Total GDP, Agro GDP and sugarcane cultivation for the years 2008, 2010 and 2012, however, There was a negative correlation between Total GDP and IPRS, indicating that economic growth did not accompany economic development, considering that for development there is a need to think beyond financial well-being but in social welfare and human development. In the analysis of Pearson's linear correlation between the Total GDP, Agro GDP and sugarcane cultivation performed between 2004 and 2013, a strong correlation was only found between the indicators Agro GDP and sugar cane cultivation , Indicating that the cultivation of sugarcane influenced only the economic growth of Agropecuária. Therefore, it is concluded that the advance of the sugarcane cultivation interfered in the economic growth of the sectors belonging to Agriculture, but did not generate positive impacts in the same proportion in the economic development of the UGRHI-22. In this sense, it is observed the need to develop and implement public policies with the purpose of making economic growth allied to economic development and thus provide well-being of the population from a financial, human and social point of view.